(untitled) (Journal of Economic Research & Business Administration, 2016)
At this time, the search for an effective unit of industrial and innova- tive development of the country continues, what is on the one hand takes place due to the strategic goal of entering the list of 30 most competitive countries in the world. The problems of effective investment policy of the enterprise are relevant to transform to industrial-innovative module for the economic development of the country. The key areas of realization is moti- vation to attract investment, improvement of legislation in the sphere of at- tracting investments, rebuilding the public investment system, development of the investment market and public-private partnerships and improving the ownership of collective forms of economic management in the state-owned enterprises. The implementation of these areas will make it possible to in- crease the production of investment income, it will affect the improvement of industrial and technological base of the enterprise, improve the efficiency of production processes and growth of industrial production. Kazakhstan adopted some programs for targeted innovation development. It is possible to organize innovation policy in manufacturing factories in Kazakhstan by increasing their efficiency and reducing the level of safety in the workplace.